Systematic Literature Review: Implementasi Model Project Based Learning terhadap Kreativitas Siswa Sekolah Dasar - Yustikasari, Rizki; Rusilowati, Ani; Widiarti, Nuni; Widiyatmoko, Arif (Jurnal Ragam Pengabdian, 2026)
This study aims to systematically examine the effect of the Project Based Learning (PjBL) model on elementary school students’ creativity. The research method used is a Systematic Literature Review (SLR) following the PRISMA procedure. Data sources were obtained from various scientific articles published between 2020 and 2026 through Google Scholar. Based on the selection process, 33 articles met the inclusion criteria and were analyzed. The results of the review indicate that the implementation of Project Based Learning (PjBL) significantly improves students’ creativity, as evidenced by the enhancement of creativity indicators such as fluency, flexibility, originality, and elaboration. In addition, PjBL is proven to be effective across various subjects and can increase students’ activeness, confidence, and critical thinking skills. No studies reported negative impacts of this model. Therefore, it can be concluded that Project Based Learning is an effective and relevant learning model to enhance elementary school students’ creativity and support 21st-century skills.